2000
DOI: 10.1016/s0960-9822(00)00742-9
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and activation of heart PFK-2 by AMPK has a role in the stimulation of glycolysis during ischaemia

Abstract: AMPK phosphorylates and activates heart PFK-2 in vitro and in intact cells. AMPK-mediated PFK-2 activation is likely to be involved in the stimulation of heart glycolysis during ischaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
542
4
9

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 728 publications
(582 citation statements)
references
References 39 publications
27
542
4
9
Order By: Relevance
“…Experimentally, and potentially clinically, this may be mediated by administration of metformin, which diminishes diabetic cardiomyopathy in a chronic type 1 diabetic model via activation of AMP kinase 43. A potential, and unexamined, benefit of sustained activation of AMP kinase may be by the phosphorylation and stabilization of PFK‐2 44. Alternatively, targeting the concerted actions of PFK‐2 and PFK‐1 more specifically may be a way to potently reverse diabetic metabolic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, and potentially clinically, this may be mediated by administration of metformin, which diminishes diabetic cardiomyopathy in a chronic type 1 diabetic model via activation of AMP kinase 43. A potential, and unexamined, benefit of sustained activation of AMP kinase may be by the phosphorylation and stabilization of PFK‐2 44. Alternatively, targeting the concerted actions of PFK‐2 and PFK‐1 more specifically may be a way to potently reverse diabetic metabolic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Deprivation of oxygen (hypoxia) is another stress that can limit catabolism, thus causing increases in AMP: ATP and AMPK activation. This occurs, for example, in cardiac muscle in response to ischaemia, an interruption in the blood supply (21)(22)(23) . Similar to what has just been described for hypoglycaemia, in most cells the oxygen tension has to drop to pathologically low levels (such as occurs during ischaemia) before AMPK is activated.…”
Section: Activation Of Mammalian Amp-activated Protein Kinase By Metamentioning
confidence: 99%
“…We first demonstrated that AMPK activation occurs during myocardial ischemia, 2,3 a finding now reproduced by numerous laboratories. 4,[7][8][9][10][11]23,24 This activation of AMPK presumably occurs as an approach to restore myocyte ATP levels, primarily turning on ATP generating pathways. It is now clear that AMPK activation can increase both glucose and fatty acid metabolism in the ischemic heart.…”
Section: Ampk Activation During Ischemia/reperfusionmentioning
confidence: 99%
“…8 AMPK also phosphorylates and activates phosphofructokinase 2, 24 which produces fructose 2,6-bisphosphate, a potent stimulator of glycolysis. As AMPK has an important role in promoting glucose uptake and glycolysis, 24,37,38 the activation of AMPK during ischemia may benefit the heart by increasing glucose utilization (and subsequently anaerobic ATP synthesis).…”
Section: Ampk Activation During Ischemia/reperfusionmentioning
confidence: 99%